Nationalism Representation of Aisyah Film: Biarkan Kami Bersaudara - Susi Setyowati; Indah Perdana Sari (Universitas Ahmad Dahlan, 2019)
This study is aimed to examine the nationalism representation of Aisyah film : Biarkan Kami Bersaudara. The film tells about education and difference of belief in the remote area. The problem that appears is one of the causes of nationalism sense in this film, but the nationalism cantt be seen directly, it is hiding behind the sign. This study is a qualitative desscriptive research with semiotic Charles Sanders Pierce approach. The research data is qualitative. The qualitative data in this research are in form of text fragments in the form of words, phrases, sentences or dialogues in the film scene that have conformity with the formulation of teh problem presented. The data source of this research is the film of of Aisyah : Biarkan Kami Bersaudara. Data collection in this study uses the listening metode using note-taking techniques. After the data collected, it is classified based on the type of problem, namely the representation of nationalisme in the film. This is done to simplify the data analysis. The data analysis technique in this research is using interpration base on triangel meaning semiotic method. Pierce is a sign, object and interpretant. The form of natonalism in this film is to sacrifice for the nation, accept pluralism, be proud of diverse cultures, and prioritize the public interest. The most dominant form of nationalism as long as pluralism is received, especially in terms of differences in religious beliefs Aisyah Film : Biarkan kami Bersaudara is one of many ways to use film media to develep a sense of nationalism.